2011
DOI: 10.1002/hed.21417
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of sinonasal squamous cell carcinoma

Abstract: The genomic profile of sinonasal SCC showed a number of chromosomal regions with copy number changes similar to those known in HNSCC, in spite of the differences in etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The genome-wide profile of gains and losses of the cell lines was similar to what has been described in primary sinonasal SCC35, including losses at chromosomal bands 3p, 4q, 8p, 10p, 13q, 18q and 21q, gains at 3q, 7p, 8q, 11q, 14q, 18p and 20q and amplification at 11q13. Most of these aberrations are also recurrent in head and neck SCC.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The genome-wide profile of gains and losses of the cell lines was similar to what has been described in primary sinonasal SCC35, including losses at chromosomal bands 3p, 4q, 8p, 10p, 13q, 18q and 21q, gains at 3q, 7p, 8q, 11q, 14q, 18p and 20q and amplification at 11q13. Most of these aberrations are also recurrent in head and neck SCC.…”
Section: Discussionsupporting
confidence: 71%
“…Most of these aberrations are also recurrent in head and neck SCC. A curious exception are gains at chromosome 5p and loss at 5q, these are very frequent in head and neck SCC but not so in sinonasal SCC35. Aside from recurrent genetic changes, we found several focal aberrations in the cell lines, both high level amplifications and homozygous deletions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, tobacco, a major risk factor for head and neck squamous cell carcinoma (HNSCC) does not have an important role in MSSCC (Zheng et al , 1993; Holt, 1994). It has been suggested that molecular mechanisms of carcinogenesis might be different for these cancers (Lopez et al , 2011). Although analyses of major cancer-related genes, such as TP53 and K-ras, mutation were reported (Bornholdt et al , 2008; Holmila et al , 2010), relatively few genome-wide gene expression analyses of MSSCC have been conducted and no analyses of microRNAs (miRNAs) have been performed for this disease.…”
mentioning
confidence: 99%
“…[8] Recently, accumulating evidence suggests that a number of genetic alterations may contribute to the initiation and progression of SNSCC. [912] The p53 gene is a tumor suppressor gene mapped to chromosome 17p13, encodes the p53 protein, which involves in the regulation of the cell cycle, the inhibition of DNA synthesis, the function of DNA repair and apoptosis. [1315] The p53 mutation is the most commonly found genetic alterations in various human carcinomas, [16,17] and the overexpression of p53 detected by immunohistochemistry (IHC) in most of cases (85%) is consistent with an underlying mutation.…”
Section: Introductionmentioning
confidence: 99%